2005
DOI: 10.1016/j.ygcen.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-MSH, the melanocortin-1 receptor and background adaptation in the Mozambique tilapia, Oreochromis mossambicus

Abstract: The regulation of skin darkness in vertebrates is mediated by alpha-melanophore-stimulating-hormone (alphaMSH). For this action, alphaMSH binds to the melanocortin (MC)-1 receptor, a 7-transmembrane receptor located in melanophore cell membranes. The Mozambique tilapia, Oreochromis mossambicus, can change the hue of its body in response to a change in background, a process that may involve alphaMSH and the MC1R. Scale melanophores were isolated from tilapia that were acclimatised for 25 days to a black, contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…It is also involved in the regulation of melanin synthesis in mammals and fish [181,182]. Along with these pigment regulatory functions, in fish alpha-MSH serves as a satiation signal in feeding behavior [183] and acts as corticotrope in the chronic phase of the stress response [184]: plasma alpha-MSH levels increase after temperature shock [185], during confinement combined with air exposure [186] and during chronic exposure to acidified water [187]. It has been reported that MSH produces melanin dispersion in melanophores by increasing the cyclic AMP content of the cell.…”
Section: Alpha-melanocyte-stimulating Hormone (Alpha-msh)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also involved in the regulation of melanin synthesis in mammals and fish [181,182]. Along with these pigment regulatory functions, in fish alpha-MSH serves as a satiation signal in feeding behavior [183] and acts as corticotrope in the chronic phase of the stress response [184]: plasma alpha-MSH levels increase after temperature shock [185], during confinement combined with air exposure [186] and during chronic exposure to acidified water [187]. It has been reported that MSH produces melanin dispersion in melanophores by increasing the cyclic AMP content of the cell.…”
Section: Alpha-melanocyte-stimulating Hormone (Alpha-msh)mentioning
confidence: 99%
“…The involvement of alpha-MSH in pigmentation in fish has been reported for several species, such as catfish, eel, trout [189], and cyprinid Zacco temmincki [190], while in Fundulus, arctic charr, flounder, gilthead sea bream and red porgy, such an involvement could not be demonstrated [189,[191][192][193][194]. The role of alpha-MSH has been demonstrated in Oreochromis mossambicus, where it binds to the melanocortin 1 receptor and can change the hue of its body in response to a change in background [195]. Interestingly, the involvement of ACTH and alpha-and beta-MSH in human skin pigmentation was first demonstrated upon systemic application on human volunteers, where these peptides were found to induce a marked skin darkening [196][197][198].…”
Section: Alpha-melanocyte-stimulating Hormone (Alpha-msh)mentioning
confidence: 99%
“…This indicates that the different components of the melanocortin system were already present before the radiation of gnathostomes, but melanocortin receptors were not yet found in non-chordate species. The action of the melanocortin system has been implicated in fish dorsal ventral pigmentation and background adaptation in several teleost fishes [79,86]. The pharmacological properties of fish MC1R and its peptide agonists appear to be very similar when compared to the mammalian system [79,85].…”
Section: Sexual Selectionmentioning
confidence: 99%
“…Morphological colour changes are produced by prolonged background adaptations and further mediated by change in size and density of chromatophores. Various studies (van der Salm et al, 2005;Logan et al, 2006;Hatamoto and Shingyoji, 2008;Shiraki et al, 2010) were performed on fish adapted to black background. An increase in number of mealnophores was observed that leads to dramatic alteration in overall colouration of fish form light to dark.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in number of mealnophores was observed that leads to dramatic alteration in overall colouration of fish form light to dark. Melanocyte-stimulating hormone (␣-MSH) from the pituitary plays an important role in the differentiation and proliferation of melanophores (Baker, 1991;Zhu and Thomas, 1996;Fujii, 2000;Halaban, 2000;van der Salm et al, 2005) whereas norepinephrine and melanin-concentrating hormone (MCH) generally cause melanin aggregation (Baker, 1991). However, adaptation to white background resulted in paler body colouration as melanophore size and number decreases.…”
Section: Introductionmentioning
confidence: 99%